Effect of immune checkpoint inhibitor time-of-day infusion on survival in advanced biliary tract cancer: a propensity score-matched analysis - Zheng, Yichen; Shi, Fanfan; Sun, Lingqi; Guo, Jiamin; Ren, Tonghui; Ma, Ji (Frontiers in Immunology, 2024)
BackgroundCircadian rhythms in the immune system and anti-tumor responses are underexplored in cancer immunotherapy. Despite the success of immune checkpoint inhibitors (ICIs) in treating advanced biliary tract cancers (BTCs), not all patients benefit. This study examined whether the timing of ICI administration affects outcomes in advanced BTC patients.MethodsWe included advanced BTC patients from West China Hospital of Sichuan University who received ≥2 ICI treatments from October 2019 to September 2023, with follow-up until May 2024. Primary outcome was overall survival (OS), with secondary outcomes including progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs). Propensity score matching (1:2 ratio, caliper width 0.1) mitigated confounding factors. Cox proportional hazards regression analyzed the impact of ICI timing (post-16:30) on OS and PFS. Chi-square test assessed ORR and AE differences.ResultsAmong 221 patients, 51 received ≥20% of ICIs after 16:30; 170 received <20%. Post-matching, 49 late-infusion patients had significantly shorter OS (median 10.1 vs. 14.5 months, HR=1.80, P=0.012) compared to 90 early-infusion patients. Pre-matching, late-infusion patients also had shorter OS (median 9.8 vs. 13.7 months, HR=1.68, P=0.010) and PFS (median 4.9 vs. 8.1 months, HR=1.62, P=0.006). Multivariate analysis confirmed these results. No significant differences were found in ORR (χ^2 = 1.53, P=0.215) or AEs (all P>0.050). Sensitivity analyses supported these findings.ConclusionTiming of ICI administration affects efficacy in advanced BTC, with pre-16:30 infusions linked to better survival. Larger, prospective studies are needed to validate these results.